A World of Many Colours: yakṣagāna rangabhūmi - Katrin Binder (Ksiegarnia Akademicka Publishing, 2016)
The present paper examines the varied and mutual influences between a local form of South Indian dance drama—the yakṣagāna dance-drama of coastal Karnataka—and forms of local ritual performances. A short description of yakṣagāna and its history is followed by a definition of the cultural spheres represented by the languages of Sanskrit, Kannada and Tulu. These spheres form the cultural configuration for mutual interaction. The paper offers exploratory discussions of “localization” as a textual strategy in yakṣagāna and the possible influences between the dance drama and the nāgamaṇḍala and būta rituals.